1, 3-Dipolar cycloaddition of vinyloxy quinolines with α-alkoxy carbonyl aldonitrones or cyclic surrogates: A comparative study for an asymmetric access to trans 4-quinolinoxy oxaprolines. Issue 3 (18th January 2019) - Hamdi, Abdelrahman; Laurent, Mathieu Y.; Hémon-Ribaud, Annie; Mostafa, Amany S.; Massoud, Mohammed A.M.; Selim, Khalid B.; Dujardin, Gilles
Abstract: The asymmetric access to unreported trans 4-quinolinoxy oxaproline precursors is investigated here in a comparative way by 1, 3-dipolar cycloaddition of vinyloxy quinolines with chiral α-alkoxycarbonyl aldonitrones and chiral cyclic surrogates. Graphical abstract: